PENINGKATAN PENGETAHUAN PETUGAS LAPANGAN DI NTB TENTANG TEKNOLOGI PAKAN TERNAK TERKINI MELALUI PROGRAM EDUKASI BERBASIS KOMUNITAS - Ria Harmayani; Dwi Kartika Risfianty; Abyadul Fitriyah; Alimuddin Alimuddin; Muhammad Nur; Ishmah Humaidatul Aminah Zaim Alyaminy; Rendy Hikmal W.; Lalu Fauzan Hamid (Bajang Institute, 2025)
The development of innovative modern feed technology, such as the use of alternative feed ingredients, feed management systems, and the development of feed banks based on agricultural waste, has great potential to improve farm efficiency and productivity. However, the success of implementing these technologies heavily depends on the knowledge and skills of field officers as well as the community of farmers in the field. Community-based outreach activities conducted by the service team in NTB demonstrate that community-based education programs are effective in increasing field officers’ knowledge regarding current feed technologies, including technological innovations and funding mechanisms. Evaluation results show a significant increase in participants’ understanding, which can potentially accelerate technology adoption and the sustainability of farming enterprises. It is recommended to expand and strengthen ongoing training programs, develop community networks, and improve access to funding schemes to support the sustainable implementation of innovative feed technologies in the region.